Establishment of a Colony of Phlebotomus argentipes under Laboratory Conditions and Morphometric Variation between Wild-Caught and Laboratory-Reared Populations - Tharaka Wijerathna; Nayana Gunathilaka; Kithsiri Gunawardena (Journal of Tropical Medicine)
The field-based studies on sand flies are not adequate to uncover information required for the control of the leishmaniasis through reduction of vector populations. Therefore, establishment and maintenance of laboratory colonies of sand flies is an essential step in leishmaniasis research. In the current study, a colony of P. argentipes was established from wild-caught sand flies following standard procedures from the published literature. Morphological measurements of laboratory-reared and wild-caught individual sand flies were compared to assess the difference between two groups. The colony was successfully established under confined laboratory conditions. The comparison of morphometric parameters revealed that the laboratory-reared sand flies are significantly larger than those caught from wild, suggesting a possibility of increased fitness of sand flies under favorable environmental conditions which may cause higher prevalence in the disease. The current study reports the first successful attempt in colonizing sand flies under laboratory conditions. However, the colony data suggest that the conditions extracted from the published literature need to be optimized to suit local settings in order to achieve maximum population sizes within the available amount of resources.